Dr. Gustavo Aldereguia Lima. A historical and social approach of his life. - Reinaldo Pino Blanco; Gerardo Rivero González; Iris González Morales; Yaquelín Torres Torrens (Medisur)
Dr. Gustavo Aldereguía Lima was a revolutionary, outstanding scientist in our milieu. This article is about his remarkable work during 75 years in two main aspects; as a tireless social fighter, and a distinguished scientist. It is our purpose to stand out some aspects of his professional work recognizing his role as a doctor, social hygienist and researcher. It is also important to point out his authentic role as a social fighter against the governors of the republic times in Cuba.